Equality in the City Imaginaries of the Smart Future - Flynn, Susan (Intellect, 2022)
This collection critiques the rhetoric of 'smart cities'. It seeks to engender a timely debate about what future cities might look like and what their concerns should be. Using a multi-disciplinary perspective, it features acclaimed scholars whose work investigates the proposed networked digital technologies that ostensibly affect planning policies, control infrastructures and deliver and manage city services and systems. The contributors offer insights into how future cities might be envisaged, planned and executed in order to be more 'equal'.